Measuring Community Satisfaction Through Smart Government and Quality of Service in Mal Pelayanan Publik - Triyandra, Annisa Citra; Riyandra, Raudhah Mutiara; Hendra, Muhammad David; Amran, Sri Oktika; Adriyani, Ayu (Jurnal Perspektif, 2024)
The implementation of smart government and improving the quality of service at the Pekanbaru City Public Service Mall is a form of implementing the smart city program carried out by the Pekanbaru City government for the community. This realization is evidenced by faster, more effective, and economical services. The efforts made by the government aim to make it easier for the public to carry out government bureaucratic affairs, which are sometimes still considered complicated. Smart government and improving the quality of services that have been carried out are expected to satisfy the community in terms of service. In this study, the author uses the S-O-R theory to make it easier for researchers to analyze existing problems. This S-O-R theory is used as a basis by researchers to see the communication process that takes place in public services where the stimulus conveyed by the message source can be received and interpreted by the target of communication or the recipient of the message in the form of perception or attitude. This study aims to determine the effect of smart government and service quality simultaneously on community satisfaction at the Pekanbaru City Public Service Mall. The research method used is quantitative,e with data collection techniques using a questionnaire with a total sample of 100 respondents taken based on a random sampling technique for data processing in this study using SPSS with multiple regression analysis techniques. Based on the results of this study, it was found that there was an influence between smart government and service quality on community satisfaction at the Pekanbaru City Public Service Mall, partially or simultaneously. The coefficient of determination test shows that the contribution of smart government influence and service quality to community satisfaction at the Pekanbaru City Public Service Mall is 0.411, which means that the smart government variable influences the community satisfaction variable and also service rate of 41.1% and the rest is influenced by other factors that are not present in this research.